STRATEGIES FOR DEVELOPING FRIENDSHIP, SOLIDARITY, AND CIVIC AWARENESS AMONG STUDENTS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article examines effective strategies for developing friendship, solidarity, and civic awareness among students within educational institutions. In the context of globalization and increasing cultural diversity, education plays a key role in fostering social cohesion, mutual respect, and active citizenship. The study analyzes the importance of positive interpersonal relationships, inclusive educational environments, civic education, and community engagement in shaping socially responsible students. The findings emphasize that systematic educational approaches contribute to harmonious coexistence, democratic participation, and long-term societal development.